Food Security Dilemma And Development Discourse in Mentawai Islands - Erwin Erwin; Ade Irwandi; Ermayanti Ermayanti (Jurnal Ilmiah Membangun Desa dan Pertanian, 2024)
The food problem in Mentawai has been a polemic since the New Order (Soeharto's government) due to the development program. The FSVA (Food Security and Vulnerability) report shows that Mentawai Islands Regency is the only food-insecure district in West Sumatra Province. This is a dilemma due to the food transition from sago to rice, the resettlement program, and forest destruction caused by timber companies. This research looks at three major areas of the Mentawai Islands: Siberut Island, Sipora Island, and Pagai Island. Through a descriptive approach, 20 informants from the three islands were selected, and interviews, observations, and a literature review were conducted. Data were analyzed step-by-step. The results show that the mission to modernize the Mentawai people has disrupted their food security. The modern development program has changed the living habits of the Mentawai people, especially regarding food. The native food of the Mentawai people switched to rice and was forced to adjust due to the scarcity of sago because the forest has been commercialized into production forests. They were also moved from traditional houses to settlements built by social programs (Resettlement of Terasing Communities). The development program becomes a discourse that binds the facts of domination, reproduction, and socio-politics. Thus, we forget the local wisdom that grows and develops in the Mentawai community about food.